Open peer review: Another step towards open science by scientific journals - Abadal, Ernest; Da-Silveira, Lúcia (Anuario ThinkEPI, 2020)
The opportunities of the application of open peer review to journals are analyzed. We discuss the characteristics and types of open peer review, the pros and cons of applying this model to journals, and the opinion of the main agents in the process (authors, reviewers, and editors). Finally, some good practice experiences that serve to complement the theoretical framework are presented.
Keywords: Open peer review; Open science; Scientific journal; Case study; MDPI; SciELO; BioMed Central; PeerJ.